2008
DOI: 10.1110/ps.083472808
|View full text |Cite
|
Sign up to set email alerts
|

Conformational gating of dimannose binding to the antiviral protein cyanovirin revealed from the crystal structure at 1.35 Å resolution

Abstract: Cyanovirin (CV-N) is a small lectin with potent HIV neutralization activity, which could be exploited for a mucosal defense against HIV infection. The wild-type (wt) protein binds with high affinity to mannose-rich oligosaccharides on the surface of gp120 through two quasi-symmetric sites, located in domains A and B. We recently reported on a mutant of CV-N that contained a single functional mannose-binding site, domain B, showing that multivalent binding to oligomannosides is necessary for antiviral activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(78 citation statements)
references
References 44 publications
3
75
0
Order By: Relevance
“…Several carbohydrate-binding proteins (lectins) have been isolated and characterized as candidates for suppressing gp120 binding to susceptible cells. Among them, cyanovirin-N (CV-N) has already been intensively investigated to determine its structural properties, carbohydrate-binding potential and antiviral activity (Bewley & Otero-Quintero, 2001;Bewley et al, 2002;Fromme et al, 2008;Tsai et al, 2004). Another lectin, griffithsin (GRFT), isolated from a red alga (Griffithsia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Several carbohydrate-binding proteins (lectins) have been isolated and characterized as candidates for suppressing gp120 binding to susceptible cells. Among them, cyanovirin-N (CV-N) has already been intensively investigated to determine its structural properties, carbohydrate-binding potential and antiviral activity (Bewley & Otero-Quintero, 2001;Bewley et al, 2002;Fromme et al, 2008;Tsai et al, 2004). Another lectin, griffithsin (GRFT), isolated from a red alga (Griffithsia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, varied CV-N complexes with different carbohydrate structure have been analysed, with ligands such as dimannose Man␣1-2Man␣ [101], oligosaccharides such as hexamannoside or Man 9 GlcNAc 2 [86] and mutated CV-N with mannose dimmers [111]. Their studies suggested the involvement of two carbohydrate binding sites (primary and secondary) in CVN having varied affinity towards oligosaccharides [101].…”
Section: N Ellipsosporum Lectin (Cyanovirin [Cvn])mentioning
confidence: 99%
“…Upon binding to gp120, Arg-76 undergoes a large conformational change, bringing its side chain from an unlocked position to a locked position, in which two direct hydrogen bonds to the ligand are formed. Glu-41 may contribute to the tight binding of the sugar and possibly in the selectivity for Manα(1-2)Manα (Fromme et al 2008). Recently, molecular-dynamics simulations in solution demonstrated no conformational preferences for Arg-76.…”
Section: In Eukaryotic Hostmentioning
confidence: 99%